Developing an English Vocabulary Material Using English Learning Application - Luthfi Abdillah, Muhammad (Academia Publication, 2023)
This research focuses on developing English vocabulary material by using English Learning Application at 1st-grade MTs. Mambaus Sholihin Gresik. The material of this product was designed according to the needs and characteristics of the students. With this material, students can learn English vocabulary easily because the application is very practical to use for learning. In this research, the researcher used the approach of Research and development, Research and development is a method used to create some product and then try it to the objective of the study about the effectiveness of the product. The data collection techniques which were used in this research were distributing questionnaires to students and interviewing the teacher. The questionnaires were applied in the needs analysis stage. The students’ characteristics and learning resources were observed by doing a need analysis. The application was effective. Students were able to increase their vocabulary and able to reduce their boredom with learning English. They also believed that the product was useful to assist them in learning vocabulary. The role of the application as a medium for learning vocabulary is very influential, this is because before learning we must pay attention to the motivation and interest of students in learning. The application is proven to be able to overcome student motivation and interest. The improvement, revision, addition, and alteration had been done based on the feedback from the expert and the subjects of the product try-out.